Increasing public awareness through routine health checks for residents of RT 21 Kelurahan 13 Ulu, Palembang - Juliastuti Juliastuti; Deni Firmansyah; Annisa Ayu Ranita; Feronica Putri Pratama; Fitri Sri Rizky; Dien Seftyarlen Dwi Utami; Dea Putri Anjelita; Desi Wijayanti; Roihana Baintan; Desi Indriani; Devi Indah Pratiwi (Community Empowerment, 2024)
Health check-ups are one of the efforts to detect abnormalities in the body that should be performed routinely with the aim of prevention and early treatment. The purpose of this activity is to increase public knowledge about the importance of health check-ups. With increased public awareness of the importance of health check-ups, their desire to undergo health checks also increases, allowing for earlier disease identification. The method used involves counseling with leaflet media and community health check-ups. Based on health screenings conducted in Kelurahan 13 Ulu RT 021 RW 005, Seberang Ulu II District, Palembang City, the results indicated an increase in knowledge, understanding, and public awareness regarding regular health checks. This is expected to encourage a change in community behavior towards routine health check-ups, leading to earlier disease detection and prevention of more serious illnesses.